Emotional processing changes of qigong on college students: A pilot ERP study of a randomized controlled trial - Qingchuan Hu; Kevin Chen; Jialei Zhang; Xiaoqian Shao; Yulong Wei (Journal of Traditional Chinese Medical Sciences, 2021)
Objective: To investigate the influence of qigong on late positive potential, which was elicited by affective pictures. Methods: College students who met the inclusion criteria were enrolled and randomly allocated to the qigong group, which received a four-week training (n = 41) or the control group (n = 41). All participants were assessed before and after the training for event-related potential, which was elicited by negative, neutral, and positive pictures. Electrodes at the centerline position of the frontal area (FCz), parietal area (Pz), and occipital area (Oz) were analyzed. Results: Negative, neutral, and positive pictures demonstrated statistically significant differences on FCz (P < .001), Pz (P < .001), and Oz (P < .001). The interaction between the group factor and time factor was statistically significant on Pz (P = .028). The pairwise comparison of Pz on the time factor and group factor showed that the amplitudes of the qigong group after training were smaller than before (P < .001), and the amplitudes of the control group were not statistically significant (P = .355). Conclusion: Our results supported the conclusion that qigong practices could affect the emotional regulation of college students. Qigong exercise weakens the emotional regulation of late positive potential, which is sensitive to top-down affective modulation. The findings imply that the regulating effect of qigong on emotions may be part of the reason why it is effective in reducing depression and anxiety symptoms.